On the robustness of the association between Honesty-Humility and dishonest behavior for varying incentives - Klein, Sina; Thielmann, Isabel; Hilbig, Benjamin E.; Heck, Daniel W. (Journal of research in personality, 2020)
Previous research consistently showed a negative link between Honesty-Humility (HH) and dishonest behavior. However, most prior research neglected the influence of situational factors and their potential interaction with HH. In two incentivized experiments (N = 322, N = 552), we thus tested whether the (subjective) utility of incentives moderates the HH-dishonesty link. Replicating prior evidence, HH showed a consistent negative link to dishonesty. However, the utility of incentives did not moderate this association, neither when manipulated through incentive size (BF01 = 5.7) nor when manipulated through gain versus loss framing (BF01 = 20.4). These results demonstrate the robustness of the HH-dishonesty link.
Gesehen am 05.11.2020